The J. Paul Getty Museum handbook of the collections. (The J. Paul Getty Museum, 1997)
This revised edition of the Handbook highlights the collections of the Getty Museum at the Getty Center, including the Museum's latest acquisitions. In recent years the paintings collection has grown substantially, and featured here are paintings new to the Getty by artists such as Claude Monet, Jean-Honore Fragonard, Nicholas Poussin, Jacques-Louis David, and Paul Cezanne, as well as recently acquired works in every department of the Museum. Three hundred forty objects are reproduced-each with information about content and style-to help enhance appreciation and insight by non-specialist readers and museum-goers alike.